Implementation of Character Education to Improve Social Skills and Emotional Intelligence in Learning in Elementary Schools - Zainuddin Zainuddin; Cut Khairani; Hamsidar Hamsidar (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
Character education is a fundamental aspect of learning in elementary school because it plays an important role in shaping students' social skills and emotional intelligence from an early age. Global developments and rapid technological advances require students to not only excel academically, but also have good social interaction skills, empathy, emotional control, and a responsible attitude. This study aims to describe and analyze the implementation of character education in learning and its contribution to improving the social skills and emotional intelligence of elementary school students. The research method used is a qualitative approach with a descriptive design. The research subjects include elementary school teachers and students, with data collection techniques through observation, and interviews. The results of the study show that the implementation of character education is carried out in an integrated manner in learning activities, school culture, and teacher examples through character values such as discipline, responsibility, cooperation, empathy, and honesty. The application of active, collaborative, and reflective learning strategies has been proven to be able to improve social interaction between students and their ability to recognize, manage, and express emotions positively. In addition, the support of the school environment and the role of teachers as character models make a significant contribution to the successful implementation of character education. The conclusion of this study confirms that character education implemented consistently and systematically can improve the social skills and emotional intelligence of elementary school students. Therefore, character education needs to continue to be developed as an integral part of learning to form students who are characterful, empathetic, and able to adapt in social life.